The Effectiveness of Financial Services Authority Supervision of Leasing Companies from the Perspective of State Administrative Law - Gunarto Wardono; Mustofa Kamil; Rahmat Wijaya; Juhana Nuryana; Raliyanto Budi Wikarno; Hikmat Ansori (International Journal of Business and Quality Research, 2026)
This study evaluates the effectiveness of the Financial Services Authority (OJK) in supervising leasing companies and identifies systemic challenges in consumer protection from an Administrative Law perspective. Employing a normative legal methodology with a contextual approach, the research analyzes primary regulations, including the OJK Law, Consumer Protection Law, Fiduciary Guarantee Law, and relevant Constitutional Court rulings, alongside documented field practices. Findings reveal a persistent implementation gap between formal regulatory mandates and practical enforcement. Despite measurable declines in consumer complaints, aggressive debt collection, unilateral fiduciary executions, and opaque contractual practices remain prevalent. From an administrative law standpoint, these shortcomings reflect vulnerabilities in applying legitimacy, proportionality, and accountability principles, compounded by regulatory fragmentation, limited institutional capacity, and weak inter-agency coordination. The study concludes that OJK’s supervisory framework requires structural reform to transition from compliance-based monitoring to outcome-oriented governance. Recommendations include harmonizing overlapping regulations, establishing joint enforcement task forces, integrating data-driven monitoring systems, and implementing sustained consumer literacy initiatives. Ultimately, aligning financial supervision with foundational administrative law tenets is essential to strengthen institutional credibility, ensure equitable consumer protection, and foster a resilient leasing sector in Indonesia.